Trabajando bajo el control del algoritmo: El caso de los repartidores de Rappi en Lima Metropolitana en el contexto de pandemia - Mogollón Barrionuevo, Natalia (2023)
The growth of the gig economy in recent years has revolutionized the world of work due to the changes that have been generated in the organization, forms of control and structure of the labor market in an increasingly flexible and technological context; However, this is accompanied by characteristics typical of job insecurity. In this context, the article seeks to answer how gig economy workers adapt and react to the forms of control and power exercised by platforms. Based on the experience of delivery people from the Rappi platform in Metropolitan Lima based on a case study, this research focuses on two important points: on the one hand, the control strategies used by the company over its workers are analyzed, taking advantage of the crisis generated by COVID-19 and, on the other hand, the immigration situation that characterizes the majority of this workforce. Thus, four forms of control are identified: the customer evaluation system, the flexibility discourse, information asymmetry, and rewards and incentives. On the other hand, it investigates the tactics and mechanisms used by delivery workers as a response to carry out, avoid and resist the degradation of working conditions. This article offers a double contribution: first, it addresses a topic little studied in a particular context such as the Peruvian one, whose labor market is characterized by being highly informal and precarious; and, secondly, it constitutes an advance in research on the relationships of control and resistance in the gig economy.